The Effect of Threads Geometry on Insertion Torque (IT) and Periotest Implant Primary Stability: A High-Density Polyurethane Simulation for the Anterior Mandible - Stefano Fanali; Margherita Tumedei; Pamela Pignatelli; Morena Petrini; Adriano Piattelli; Giovanna Iezzi (Crystals, 2021)
The implant geometry provides a key role in the osseointegration process and is able to improve the mechanical interaction and primary stability into the bone tissue. The aim of the present investigation was to compare different implant profiles to evaluate their influence on the primary stability on high-density polyurethane block. Methods: A total of 100 implants were used on 20 pcf polyurethane density in the present investigation, i.e., 20 implants for each of 5 groups (A, B, C, D, and E), characterized by different thread pitch and geometry. The insertion torque (IT), and Periotest mean values were recorded during the implant positioning. Results: Mean values for insertion torque values were higher for the group C and group E implant profiles when compared to all other groups (p < 0.01). No significant differences were detected between these two groups (p < 0.05). Lower IT (<20 Ncm2) were presented by groups A, B, and D (p < 0.05). All groups showed negative Periotest values. Group C implants showed the lowest level of Periotest values (p < 0.05). No significant Periotest differences were found between group B and group D and between group A and group E (p > 0.05). Conclusions: Implants with a wider and V-thread profile and a round apex showed a higher stability in a standardized polyurethane foam. Their use could be suggested in high-density bone in clinical practice.